Automatic Safety Emergency Barricade - Jenni Ria Rajagukguk; Wanda Kurniawan (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study aims to design and evaluate an Automatic Safety Emergency Barricade (ASEB) system to prevent the spread of hazardous chemical spills and improve industrial workplace safety. The research employed an experimental engineering approach through prototype development integrating a microcontroller, water level sensor, linear motor actuator, and manual pushbutton control. Data were collected through controlled laboratory testing involving sensor resistance measurements at liquid levels of 0–5 cm, 10 system accuracy trials, and barrier response-time observations. The results show that the sensor exhibited a consistent inverse relationship between liquid height and resistance value, while the system achieved 100% detection accuracy. The barricade required approximately 40 seconds to close and 36 seconds to open, indicating effective automated emergency response performance for industrial safety management.